AB0674 CLINICAL AND IMAGING FEATURES IN SPONDYLOARTHRITIS PATIENTS WITH AND WITHOUT HLA-B27 AND HLA-B51. (2nd June 2020) - Carubbi, F.; Alunno, A.; Conforti, A.; Bonifacio, A. F.; Cipriani, P.; Gerli, R.; Giacomelli, R.
Abstract : Background: Despite being commonly expressed in the general population, the human leucocyte antigen (HLA)-B27 allele strongly increases the susceptibility to develop spondyloarthritis (SpA). Likewise, the association between the HLA-B51 allele and the development of Behçet's disease is well documented. However, the exact mechanisms responsible for their pathologic role are still a matter of debate. Moreover, anecdotal reports show an association between HLA-B51 and the clinical spectrum of SpA. Objectives: To investigate the clinical and imaging findings of SpA patients according to the absence or presence of HLA-B27 or HLA-B51. Methods: We retrospectively analyzed 236 patients with axial or peripheral SpA, according to the ASAS criteria, referring to two tertiary Rheumatology Clinics between 2017 and 2019. All patients had been tested for HLA-B alleles. Patients with HLA-B51 haplotype and fulfilling the criteria for Behçet's disease were excluded. Results: Table 1 shows demographic and clinical features of patients, according with the HLA-B haplotype (neither HLA-B27 nor -B51, double negative; positive for HLA-B27 only, positive for HLA-B51 only). Inflammatory low back pain and sacroiliitis, assessed by X-ray or magnetic resonance imaging (MRI), were more prevalent in double negative and HLA-B27 patients, compared to HLA-B51 patients. In this regard, the presence of HLA-B51 was negatively associated with axial manifestations at onset (OR 0.347, 95% CI 0.200-0.604, p<0.0001) and in the course of the disease (low back pain: OR 0.395, 95% CI 0.225-0.689 p<0.0001; sacroiliitis on imaging: OR 0.342 CI 0.189-0.619 p<0.0005). When considering extra-articular manifestation, aphtous lesions were more prevalent in patients with HLA-B51 (p< 0.0001), inflammatory bowel diseases in the double negative group (p=0.0006), and increased C-reactive protein in double negative and HLA-B27 patients (p=0.02). Conclusion: The presence of HLA-B51 identifies a subgroup of SpA patients with peculiar features compared to double-negative or HLA-B27 SpA patients. HLA-B51-related SpA may be an additional condition to be included in the SpA spectrum. References: [1]Bodis G, et al. Role of Human Leukocyte Antigens (HLA) in Autoimmune Diseases. Rheumatol Ther 2018;5:5–20. [2]Rudwaleit M, et al. The development of Assessment of SpondyloArthritis international Society classification criteria for axial spondyloarthritis (part II): validation and final selection. Ann Rheum Dis 2009;68:777–83. [3]Rudwaleit M, et al. The Assessment of SpondyloArthritis International Society classification criteria for peripheral spondyloarthritis and for spondyloarthritis in general. Ann Rheum Dis 2011;70:25–31. [4]Maksymowych WP, et al. MRI lesions in the sacroiliac joints of patients with spondyloarthritis: an update of definitions and validation by the ASAS MRI working group. Ann Rheum Dis. 2019;78:1550-1558. Disclosure of Interests: Francesco Carubbi Speakers bureau: Francesco Carubbi received speaker honoraria from Abbvie and Celgene outside this work., Alessia Alunno: None declared, Alessandro Conforti: None declared, Angelo Francesco Bonifacio: None declared, Paola Cipriani Grant/research support from: Actelion, Pfizer, Speakers bureau: Actelion, Pfizer, Roberto Gerli: None declared, Roberto Giacomelli Grant/research support from: Actelion, Pfizer, Speakers bureau: Abbvie, Roche, Actelion, BMS, MSD, Ely Lilly, SOBI, Pfizer